THE EFFECT OF DESTINATION ATTRACTIVENESS, DESTINATION SERVICE QUALITY AND TOURIST SATISFACTION ON THE INTENTION OF REVISIT TO KOTA LAMA SEMARANG - Muhammad Nastabiq; Harry Soesanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study was to examine the factors that tend to influence the behavior of interest in returning to a destination. This study develops a problem regarding how the quality of destination services and destination attractiveness can positively affect tourist loyalty in terms of interest in returning to visit. This study uses 2 types of research data, namely primary data and secondary data. In this research, the population determined is the people who visit the Kota Lama Semarang tour who have visited more than 3 times. This research uses analytical techniques that are quantitative analysis using the Structural Equation Model (SEM) technique as a statistical instrument to test various hypotheses that have been determined. The results of this study indicate that destination attractiveness affects tourist satisfaction; destination service quality affects tourist satisfaction; This study cannot prove the effect of destination attractiveness on interest in returning to visit; however, this research can prove the influence of destination service quality on interest in returning to visit; and the influence of tourist satisfaction influences the interest in returning to visit. Keywords : Destination attraction; Quality of Service; Destination Service Quality; Tourist Satisfaction; SEM